2015
DOI: 10.1186/s12891-015-0492-7
|View full text |Cite
|
Sign up to set email alerts
|

Does integrity of the lesser trochanter influence the surgical outcome of intertrochanteric fracture in elderly patients?

Abstract: BackgroundMost surgeons do not fix the lesser trochanter when managing femoral intertrochanteric fractures with intramedullary nails. We have not found any published clinical studies on the relationship between the integrity of the lesser trochanter and surgical outcomes of intertrochanteric fractures treated with intramedullary nails. The purpose of this study was to evaluate the impact of the integrity of the lesser trochanter on the surgical outcome of intertrochanteric fractures.MethodsA retrospective revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 9 publications
2
16
1
Order By: Relevance
“…As demonstrated in our study, patients in Group B had statistically significant higher complication rate than result of Groups A and C. However, no significant differences were observed in complication rate between Groups A and C, which suggested that complication rate decreased after displaced lesser trochanter reduced operatively in the treatment of trochanteric fractures with intramedullary fixation. Liu et al [ 18 ] reported a comparable complication rate between patients with and without integrity of the lesser trochanter, which partially contradicted with our result. We believed that the thigh pain was analyzed and recorded as complication in our study, and no significant difference was found after thigh pain was excluded.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As demonstrated in our study, patients in Group B had statistically significant higher complication rate than result of Groups A and C. However, no significant differences were observed in complication rate between Groups A and C, which suggested that complication rate decreased after displaced lesser trochanter reduced operatively in the treatment of trochanteric fractures with intramedullary fixation. Liu et al [ 18 ] reported a comparable complication rate between patients with and without integrity of the lesser trochanter, which partially contradicted with our result. We believed that the thigh pain was analyzed and recorded as complication in our study, and no significant difference was found after thigh pain was excluded.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the surgical time was also significantly longer in Group C compared with Groups A and B. That was also in accordance with previous studies, which indicated that trochanteric fractures of A2 and A3 needed a longer operative time [ 18 , 26 , 27 ]. We believed that trochanteric fractures with displaced lesser trochanter treated with intramedullary fixation were much more technically demanding, especially when operative reduction of the displaced lesser trochanter was required.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This would reduce the risk of loss of fracture reduction, penetration of the hip screw or varus deformity. In fact, there is biomechanical evidence from an in vitro study [ 21 ] that refixation of the lesser trochanter increases primary stability of pertrochanteric fracture osteosynthesis. In a recent published retrospective study, 22 patients with intertrochanteric fractures and lesser trochanter fragment displacement where treated surgically with proximal IM nailing and with a wiring technique for reduction and fixation of the lesser trochanter [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…50% cases of hip fractures are extra capsular Intertrochanteric femoral fractures in geriatric population [4] . This needs early mobilization to prevent medical co-morbidies and regain preinjury activity operative management have become preferred [5] .…”
Section: Introductionmentioning
confidence: 99%